2020
DOI: 10.1017/s0022149x20000553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geographical and climatic factors on cystic echinococcosis in south-western Iran

Abstract: Cystic echinococcosis (CE) is caused by the larval form of Echinococcus granulosus that can cause serious health and economic problems in the endemic foci. CE is globally distributed in various climatic conditions from circumpolar to tropical latitudes. Iran is an important endemic area with a spectrum of weather conditions. The aim of this study was to determine the effects of geo-climatic factors on the distribution of livestock CE in south-western Iran (SWI) in 2016 to 2018. Data of livestock CE were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…In the present study, using geographically weighted regression analysis, the correlation between temperature, relative humidity, NDVI and the incidence of human hydatidosis was investigated. In Ilam, Semnan, Hamedan, Qazvin, and Ardabil provinces, the highest correlation was observed between temperature, relative humidity, and NDVI with the incidence of hydatidosis, which is similar to other studies (30)(31)(32). The results of Danson et al study showed the application of GIS in the study of human parasitic infections is very useful and shows a better understanding of parasite transmission.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, using geographically weighted regression analysis, the correlation between temperature, relative humidity, NDVI and the incidence of human hydatidosis was investigated. In Ilam, Semnan, Hamedan, Qazvin, and Ardabil provinces, the highest correlation was observed between temperature, relative humidity, and NDVI with the incidence of hydatidosis, which is similar to other studies (30)(31)(32). The results of Danson et al study showed the application of GIS in the study of human parasitic infections is very useful and shows a better understanding of parasite transmission.…”
Section: Discussionsupporting
confidence: 81%
“…The adult worms are inhabitants in the intestine of dogs and other canid families as the final hosts. 1 , 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has classified it as the most prevalent global food‐borne disease. 6 , 7 According to the WHO, Iran is considered one of the hyperendemic areas of the disease due to the high rate of dogs' exposure to livestock ( 3 , 4 ). The prevalence of hydatid cysts in the intermediate host was reported at 11.5%–34.6% and the incidence of 5% in human have been reported from different parts of Iran.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations